Three‐dimensional displacement field of the 2015 Mw8.3 Illapel earthquake (Chile) from across‐ and along‐track Sentinel‐1 TOPS interferometry. Issue 6 (24th March 2016) - Grandin, R.; Klein, E.; Métois, M.; Vigny, C.
Abstract: Wide‐swath imaging has become a standard acquisition mode for radar missions aiming at applying synthetic aperture radar interferometry (InSAR) at global scale with enhanced revisit frequency. Increased swath width, compared to classical Stripmap imaging mode, is achieved at the expense of azimuthal resolution. This makes along‐track displacements, and subsequently north‐south displacements, difficult to measure using conventional split‐beam (multiple‐aperture) InSAR or cross‐correlation techniques. Alternatively, we show here that the along‐track component of ground motion can be deduced from the double difference between backward and forward looking interferograms within regions of burst overlap. "Burst overlap interferometry" takes advantage of the large squint angle diversity of Sentinel‐1 (∼1°) to achieve subdecimetric accuracy on the along‐track component of ground motion. We demonstrate the efficiency of this method using Sentinel‐1 data covering the 2015 M w 8.3 Illapel earthquake (Chile) for which we retrieve the full 3‐D displacement field and validate it against observations from a dense network of GPS sensors. Key Points: Sentinel‐1 wide‐swath mode can be used to compute along‐track horizontal displacement within burst overlap regions Along‐track and across‐track interferometry on ascending and descending passes provide four different viewing geometries Validation with GPS data shows that all three components of surface displacement are resolved with subdecimetric accuracy